Maternal Obesity Management Using Mobile Technology: A Feasibility Study to Evaluate a Text Messaging Based Complex Intervention during Pregnancy - Hora Soltani; Alexandra M. S. Duxbury; Madelynne A. Arden; Andy Dearden; Penny J. Furness; Carolyn Garland (Hindawi Limited, 2015)
Background. Maternal obesity and excessive gestational weight gain (GWG) are on the rise with negative impact on pregnancy and birth outcomes. Research into managing GWG using accessible technology is limited. The maternal obesity management using mobile technology (MOMTech) study aimed at evaluating the feasibility of text messaging based complex intervention designed to support obese women (BMI ≥ 30) with healthier lifestyles and limit GWG. Methods. Participants received two daily text messages, supported by four appointments with healthy lifestyle midwife, diet and activity goal setting, and self-monitoring diaries. The comparison group were obese mothers who declined to participate but consented for their routinely collected data to be used for comparison. Postnatal interviews and focus groups with participants and the comparison group explored the intervention's acceptability and suggested improvements. Results. Fourteen women completed the study which did not allow statistical analyses. However, participants had lower mean GWG than the comparison group (6.65 kg versus 9.74 kg) and few (28% versus 50%) exceeded the Institute of Medicine's upper limit of 9 kg GWG for obese women. Conclusions. MOMTech was feasible within clinical setting and acceptable intervention to support women to limit GWG. Before further trials, slight modifications are planned to recruitment, text messages, and the logistics of consultation visits.